More staff = better quality of life for people with dementia? results of a secondary data analysis in German shared-housing arrangements - Johannes Gräske; Annika Schmidt; Karin Wolf-Ostermann (BMC, 2019)
Abstract Background Shared-housing arrangements (SHAs) in Germany are an alternative care arrangement for people with dementia. They are disconnected from traditional nursing homes and are often situated in ordinary apartment buildings. Community health care providers serve persons with dementia in SHAs, and there is no official regulation regarding the staff-resident ratio. The association between the staff-resident ratio and the quality of life (QoL) of persons with dementia has not yet been investigated in SHAs. Method A cross-sectional study was performed in SHAs in Berlin, Germany, using ANCOVA models to analyse whether residents' QoL (QUALIDEM), as assessed by staff in SHAs, can be explained by the staff-resident ratio, adjusted for residents' sex, age, length of stay, challenging behaviour (CMAI), cognitive impairment (GDS) and level of care dependency according to the German statutory health care insurance. Results In this study, 58 SHAs with 396 residents (mean age 78.4 years, 69.4% female) participated. The staff-resident ratio was 0.2 and 0.6 for registered nurses and certified nursing assistants, respectively. Associations with QoL were found predominantly for challenging behaviour and cognitive impairment. The analysis showed that there was no significant effect of the total staff-resident ratio (p > 0.05) in explaining the variation in residents' QoL (total and subdomains). In general, the proportion of explained variance was weak (R2 <  0.216). Conclusions The present study did not show a significant association between staffing and residents' QoL in SHAs. However, further investigation is required regarding the direct interaction between staff and residents. A main focus should be to educate users about the benefits and disadvantages of shared-housing arrangements.